2008
DOI: 10.1007/s00520-008-0507-0
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile-associated disease in children with solid tumors

Abstract: CDAD may be a complication of children with solid tumours. Since this disease may be life threatening and cause epidemic clusters, this possibility must be kept in mind for the differential diagnosis of abdominal diseases in children with cancer, especially in absence of neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
1
24
0
3
Order By: Relevance
“…Most reported cases have been associated with haematological malignancies, but a recent Italian study demonstrated that 6 % of children with solid tumours had C. difficile toxin A in their stools and gastrointestinal symptoms, with three out of nine of these being under 1 year old [93]. An earlier prospective study of oncology patients demonstrated higher rates of toxin detection in asymptomatic (19 %) than in symptomatic (8.7 %) children, questioning the significance of C. difficile as a pathogen in this patient group [74].…”
Section: Children With Co-morbiditiesmentioning
confidence: 96%
“…Most reported cases have been associated with haematological malignancies, but a recent Italian study demonstrated that 6 % of children with solid tumours had C. difficile toxin A in their stools and gastrointestinal symptoms, with three out of nine of these being under 1 year old [93]. An earlier prospective study of oncology patients demonstrated higher rates of toxin detection in asymptomatic (19 %) than in symptomatic (8.7 %) children, questioning the significance of C. difficile as a pathogen in this patient group [74].…”
Section: Children With Co-morbiditiesmentioning
confidence: 96%
“…Similarly, metronidazole was the treatment of choice in an Italian prospective study of CDI in children with solid tumours and lymphomas. 7 None progressed to pseudomembranous colitis or died. C. difficile was the only pathogen found in two cases of severe enterocolitis reported from one centre.…”
Section: Treatment and Outcomementioning
confidence: 99%
“…7 The age range was 11 monthse17 years (median 5.5 years). All had abdominal pain and 8 had diarrhoea, though none progressed to pseudomembranous colitis and none died.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…The risk factors associated with C. difficile infection include recent antibiotic therapy, prolonged hospitalization, advanced age, and immunosuppression [3]. Children with solid tumors, children who underwent organ transplantation, and children with inflammatory bowel disease (IBD) are also at increased risk [4,5,6]. IBD patients are particularly challenging as their active disease is often indistinguishable from the clinical presentation of infection with C. difficile [7].…”
Section: Introductionmentioning
confidence: 99%